Os tempos da cidade entre quaresma e o carnaval. A micarême de Laranjeiras (SE) entre as décadas de 1930 a 1945 - Oliveira, Hildênia Santos de (2015)
The paper presents a study on the Carnival celebrations in Brazil, the shrovetide Carnival professionalization in the capital of the country, with the focus to the Micarême of Laranjeiras/SE-Brazil, in the decades of 1930/1945, period of emergence and Structuration of the Carnival celebration in the city, and from that party, to understand how the Carnival and its professionalization influenced the creation of the Micarême. The Micarême of Laranjeiras/SE so configured as a Carnival party that occurs since 1930, emerging from soccer teams in the city, and with the influence of cultural manifestations in municipality of Laranjeiras. Understand how the policies of Government of Getúlio Vargas, which was used not only of the Carnival, but also from the radio and football, in an attempt of a construction of a national identity interfered in party configures the primary objective of this research.